Answers

2014-09-19T14:39:13+05:30
We know that...
tan45 = 1, 
tan44 * tan46 = 1 
... 

==> 
                       log (tan1)*(tan2) * ... * tan(89) = log (1 * 1 * ... * 1) = log 1 = 0
2 3 2
Please my mark my Brainlliest ...................
2014-09-19T15:20:00+05:30
Log(tan1.tan2.tan3).................tan89)
=Log(tan1.tan89.tan2.tan88.tan3.tan87..........tan44.tan46.tan45)
=Log{tan1.tan(90-1).tan2.tan(90-2).tan3.tan(90-3)...........tan44.tan(90-46).tan45
=Log(tan1.cot1 . tan2.cot2. tan3.cot3 .........tan44.cot44.tan45)
=Log(1*1*1**.......1*1)
=log1 = 0
2 5 2